Decolonising the Indigenised curricula: preparing Australian graduates for a workplace and world in flux. Issue 5 (29th July 2022) - Bullen, Jonathan; Flavell, Helen
ABSTRACT: This article argues that current Australian graduate attributes – the strategy for assuring graduate employability – are inherently and uncritically Western and privilege white subjectivity. Drawing on Moreton-Robinson's critique of whiteness in Australian academia we challenge the idea that all students must achieve the same narrow list of generic attributes informed, we argue, by Western traditions. In doing so, we aim to create a space to explore Nakata's cultural interface as a means to simultaneously deliver key capabilities essential for future work and expand the sector's thinking beyond assuring a singular kind of graduate. Decolonising processes led by local Elders, based in authentic relationships forged at the cultural interface, we argue, would assist Australian universities to overcome tokenistic approaches to 'Indigenising the curriculum' and the challenges of 'assuring' graduate attributes. Through reimagining approaches to graduate employability, we explore how learning experiences informed by local place-based Aboriginal values, principles and perspectives present an opportunity to develop graduates equipped to reimagine themselves in response to a world and workplace in flux.